The cuproptosis related genes signature predicts the prognosis and correlates with the immune status of clear cell renal cell carcinoma - Sun, Peng; Xu, Hua; Zhu, Ke; Li, Min; Han, Rui; Shen, Jiran; Xia, Xingyuan; Chen, Xiaojuan; Fei, Guanghe; Zhou, Sijing; Wang, Ran (Frontiers in Genetics, 2022)
Clear cell renal cell carcinoma (CCRCC), also known as kidney renal clear cell carcinoma (KIRC), has a high incidence and, despite multiple treatments, a poor prognosis. Cuproptosis, an independent pattern of cell death associated with copper, plays an important role in cancer proliferation and metastasis. The role of cuproptosis-related genes (CRGs) in CCRCC is unclear. The aim of this article was to evaluate the association between CRGs levels and CCRCC prognosis using publicly available RNA-sequencing datasets. After dividing the training and testing cohort, a 4-CRGs risk signature (FDX1, DLD, DLAT, CDKN2A) was identified in the training cohort using Least absolute shrinkage and selection operator (LASSO) and Cox regression analysis. The effect of the 4-CRGs risk signature on prognosis was assessed using Kaplan-Meier (KM) curves and time-dependent receiver operating characteristic (ROC) curves and verified using the testing cohort. For different risk groups, the immune microenvironment was assessed using the CIBERSORT algorithm, and the ssGSEA method was used to assess immune function. The TIDE database and immune checkpoint expression data were used to assess the likelihood of immune escape. We found significant differences in overall survival, immune status, and drug sensitivity between high and low risk groups differentiated by 4-CRGS signature. Finally, a competitive endogenous RNA (ceRNA) network was constructed using miRTarbase and starBase databases to identify molecules that may have a regulatory relationship with CRCCC. In summary, the 4-CRGs risk signature provides a new method to predict the prognosis of patients with CCRCC and the effect of immunotherapy. We propose a new cuproptosis-associated ceRNA network that can help to further explore the molecular mechanisms of CCRCC.